The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00115-015-4401-y
|View full text |Cite
|
Sign up to set email alerts
|

„Visual snow“

Abstract: Beim "visual snow" handelt es sich um einen bisher wenig bekannten Beschwerdekomplex noch unklarer Ätiologie, der durch ein anhaltendes Flimmern ungerichtet tanzender weißer und schwarzer Punkte im gesamten binokulären Gesichtsfeld gekennzeichnet ist und von Betroffenen mit dem Rauschen eines schlecht eingestellten, flimmernden alten Röhren-fernsehgerätes verglichen wird. Diese Beschreibung wurde namensgebend für das Erkrankungsbild, das über diese umschriebene visuelle Störung hinausgeht. Um das Krankheitsbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Between 52% ( 13 ) and 72% ( 11 ) of patients with VSS also suffer from migraine. In several clinical studies, patients reported migraine attacks in association with the appearance or the aggravation of their VSS ( 4 , 11 , 14 , 16 , 36 ). Schankin et al ( 4 ) and Puledda et al ( 11 ) explored the relationship between migraine status and the manifestation of VSS and found that people with migraine tended to have more symptoms as a marker of a stronger affection by this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Between 52% ( 13 ) and 72% ( 11 ) of patients with VSS also suffer from migraine. In several clinical studies, patients reported migraine attacks in association with the appearance or the aggravation of their VSS ( 4 , 11 , 14 , 16 , 36 ). Schankin et al ( 4 ) and Puledda et al ( 11 ) explored the relationship between migraine status and the manifestation of VSS and found that people with migraine tended to have more symptoms as a marker of a stronger affection by this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Our search yielded 55 articles, most of which were reviews. Seven papers [3,[9][10][11][12][13][14] proposed clinical and electrophysiological tests in diagnostic criteria, including a web-based survey study, case-control study, and retrospective case series. Table 1 summarizes the baseline clinical characteristics of patients with VSS reported in these clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…VSS is not an isolated entity but frequently related to other entities. In most publications [3,[9][10][11][12][13][14], it is reconstituted as an entity different from migraine, although often associated with it. For approximately twothirds of the patients, symptoms progress to a series of episodes.…”
Section: Resultsmentioning
confidence: 99%
“…Für Migräne werden multisensorische, insbesondere visuelle Symptome beschrieben. Visuelle Phänomene können differenzialdiagnostisch bei Augenkrankheiten, Epilepsie, drogeninduziert und bei einigen psychiatrischen Krankheiten auftreten [33].…”
Section: Auditive Auraunclassified